Marital Patterns and Income Inequality - Arnaud Dupuy; Simon Weber (Institute of Labor Economics (IZA), 2018)
We investigate the role of marital patterns in explaining rising income inequality using a structural marriage matching model with unobserved heterogeneity. This allows us to consider both the extensive and intensive margins of the marriage market, i.e. who remains single and who marries whom. Using US data from 1962 to 2017, we show that marital patterns can explain about 1/3 of the rise in income inequality. The intensive margin (educational assortative mating) has only played a minor role (5%), the extensive margin being the main driver of the contribution of marital patterns (95%).
Keywords: C78; D1; D3; I24; J12; 330; marriage market; matching; singles; assortative mating